Unsafe temperatures, unsafe jobs: The impact of weather conditions on work-related injuries - Mattia Filomena; Matteo Picchio (Global Labor Organization (GLO), 2023)
We estimate the impact of temperatures on work-related accident rates in Italy by using daily data on weather conditions matched to administrative daily data on work-related accidents. The identification strategy of the causal effect relies on the plausible exogeneity of short-term daily temperature variations in a given spatial unit. We find that both high and cold temperatures impair occupational health by increasing workplace injury rates. The positive effect of warmer weather conditions on work-related accident rates is larger for men, in manufacturing and service sectors, and for workplace injuries. Colder temperatures lead to a substantial increase in commuting accidents, especially during rainy days.
Keywords: J28; J81; Q52; Q54; 330; climate change; temperatures; weather conditions; work-related accidents; job safety